2019
DOI: 10.15171/jhp.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Achillea millefolium aqueous extract on memory deficit and anxiety caused by stroke in ovariectomized rats

Abstract: Introduction: Some studies indicated that the decrease of estrogen level in menopausal woman results in increasing the risk of stroke. Although estrogen is a neuroprotective factor, high consumption of this compound may develop breast cancer and endometriosis. The present study investigated the effect of Achilles millefolium extract, containing estrogenlike compounds, on memory impairment and anxiogenic-like behaviors caused by cerebral ischemia in ovariectomized rats. Methods: Permanent middle cerebral artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In folk and modern medicine, alcoholic and aqueous extracts from herb and flowers as well as A. millefolium EO are used for the treatment of skin disorders in renal injury [31] and memory disorders [32], for a reduction of the intensity and duration of menstrual bleeding [33], and in many other diseases [21,[34][35][36]. Previous studies have shown that yarrow is generally safe and well tolerated by the human organism [37]; however, when used in excess, it may cause headaches and/or stupor [38] and trigger allergic contact dermatitis [39].…”
Section: Introductionmentioning
confidence: 99%
“…In folk and modern medicine, alcoholic and aqueous extracts from herb and flowers as well as A. millefolium EO are used for the treatment of skin disorders in renal injury [31] and memory disorders [32], for a reduction of the intensity and duration of menstrual bleeding [33], and in many other diseases [21,[34][35][36]. Previous studies have shown that yarrow is generally safe and well tolerated by the human organism [37]; however, when used in excess, it may cause headaches and/or stupor [38] and trigger allergic contact dermatitis [39].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, interest in various types of complementary medicine and herbal medicine has been increasing around the world [13][14][15][16][17][18][19]. Medicinal plants are a rich source of bioactive ingredients that are used to treat various diseases [20][21][22][23][24], including mental disorders such as anxiety, stress, depression, and various types of pains like headache, migraine, and toothache [23][24][25]. One of the controversial issues regarding medicinal plants is local knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, interest in various types of complementary medicine and herbal medicine has been increasing around the world [13][14][15][16][17][18][19]. Medicinal plants are a rich source of bioactive ingredients that are used to treat various diseases [20][21][22][23][24], including mental disorders such as anxiety, stress, depression, and various types of pains like headache, migraine, and toothache [23][24][25]. One of the controversial issues regarding medicinal plants is local knowledge.…”
Section: Introductionmentioning
confidence: 99%